Effect of the PRECEDE Model Concept Application Program on Stroke Prevention Behaviors among Hypertension Patients - Rakson, Kwannapa; Laeiad, Sirichay; Posakaboot, Saowanee; Rukkua, Patthama; Lounseng, Kiatinan; pitaknirapan, Somruetai (Health Science Journal of Thailand, 2025)
This quasi–experimental research aimed to study effectiveness of the PRECEDE model concept application program on stroke Prevention Behaviors. The participants consisted of Hypertension patients. The samples were divided into two groups, 31 participants each. The experimental group received the program for 8 weeks and the control group received 1 session of health education. The research experimental instruments included the intervention was the PRECEDE model concept application program on stroke prevention behaviors. The tools used for data collection consisted of general information, the health behaviors 3Aor 2Sor questionnaires and sphygmomanometer (digital blood pressure monitor). Data were analyzed by descriptive statistics. The hypothesis was tested with Wilcoxon (Matched Paired) singed ranks test and Mann-Whitney U test. The results showed that after the experiment, the experimental group had a median score of stroke prevention behaviors was significantly better than before (p-value <0.001) and had a significantly lower systolic blood pressure than before (p-value =0.001), and the stroke prevention behaviors of the experimental group was better than the control group (p-value <0.001). In addition, the systolic blood pressure values between the experimental group and the control group were significantly different (p-value <0.001), and the diastolic blood pressure were not different. The program should be implemented to change the health behaviors of patients with hypertension in other areas, and the behavior changes should be continuously monitored.